An investigation into working behavior characteristics of parabolic CFST arches applying structural stressing state theory - Shi, Jun; Yang, Kangkang; Zheng, Kaikai; Shen, Jiyang; Zhou, Guangchun; Huang, Yanxia (Journal of Civil Engineering and Management, 2019)
This paper conducts the experimental and simulative analysis of stressing state characteristics for parabolic concretefilled steel tubular (CFST) arches undergoing vertical loads. The measured stain data is firstly modeled as the generalized strain energy density (GSED) to describe structural stressing state mode. Then, the normalized GSED sum Ej,norm at each load Fj derives the Ej,norm-Fj curve reflecting the stressing state characteristics of CFST arches. Furthermore, the Mann-Kendall criterion is adopted to detect the stressing state change of the CFST arch during its load-bearing process, leading to the revelation of a vital stressing state leap characteristic according to the natural law from quantitative change to qualitative change of a system. The revealed qualitative leap characteristic updates the existing definition of the CFST arch’s failure load. Finally, the accurate formula is derived to predict the failure/ultimate loads of CFST arches. Besides, a method of numerical shape function is proposed to expand the limited strain data for further analysis of the stressing state submodes. The GSED-based analysis of structural stressing state opens a new way to recognize the unseen working behavior characteristics of arch structures and the updated failure load could contribute to the improvement on the structural design codes.